Evaluation of the carcinofauna in the rocky intertidal of Santa Elena and Guayas, Ecuador - Ramos-Veliz, John (2023)
Over the years, crustaceans have colonized various ecosystems, including the rocky marine intertidal, thanks to their adaptive capacity; however, the lack of information and studies regarding this taxon makes it difficult to know its diversity and the state of its populations. Therefore, the objective was to evaluate the carcinofauna of four rocky beaches that have geomorphological differences in the provinces of Guayas and Santa Elena, Ecuador, including their relationship with physicochemical parameters of the water through an ecological analysis with sampling based on transects and quadrats. The results indicated that these parameters do not affect the distribution and presence of crustaceans, but rather, the structural shape of the beaches, indicating that the most heterogeneous beaches harbor a greater carcinological diversity due to the variety of evolutionary morphological adaptations that some have crustaceans.